(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2015)
How does critical thinking, critical theory and critical pedagogy relate to building peace? Peacebuilding is changing. Change is happening conceptually – from the international to the local (MacGinty 2013), spatially –from the global north to the global south (Richmond 2011), and temporally –from post-conflict to pre-conflict (Boutros-Ghali 1995). The past perceptions of peacebuilding as an intervention that happens after violent conflict have tomake space for more inclusive, rooted and preventive measures – such as peace education – that seek to transform violent aspects of societies from within – so that violent conflicts do not materialize. In this essay the theoretical constructs of critical literacy, critical theory and critical pedagogy will beexamined to illuminate how critical pedagogy in peace education provides practical applications of transforming cultural and symbolic forms of violence when peacebuilding through education. By doing so, this essay considers that although critical literacy provides students the capacity to approach learning materials and identify power and inequality, and, while critical theory is important in delineating discrimination and oppression, critical pedagogy in peace education transcends the recognition of diversity to result in solidarity; or, said another way, critical literacy creates recognition, critical theory takes sides (the side of the oppressed) and critical pedagogy in peace education eliminates impediments to genuine unanimity.